104 SPONTANEOUS ILIOPSOAS TENDON RUPTURE AND PSOAS HAEMATOMA ON ASPIRIN MONOTHERAPY: A CASE REPORT. (25th October 2022) - Murphy, E; Lopez, M; Fallon, A
Abstract: Background: Spontaneous Iliopsoas Tendon (IPT) rupture is a rare condition, with a prevalence of 0.66%, occurring most commonly in athletes. Risk factors for non-athletic IPT rupture include age, female gender and steroid use. Psoas haematomas are associated with surgery, anticoagulation and coagulopathies. Only a handful of case reports have associated psoas haematoma with single antiplatelet use. We present the case of a patient who developed psoas tendon rupture and psoas haematoma. Methods: A 77-year-old female presented with a four week history of declining mobility and left hip pain, without history of trauma. Past medical history included chronic lymphoedema and an NSTEMI, for which she was taking aspirin monotherapy. On examination, she had reduced power on left hip flexion and a tender anterior thigh, with normal sensation. CT showed asymmetric thickening of the left iliacus muscle and surrounding fat stranding. MRI demonstrated partial IPT tear with oedema extending into the iliacus muscle. Results: After several weeks of rehabilitation, her mobility deteriorated again. A second CT was performed, which showed new expansion and fat stranding of the right iliopsoas muscle and tendon compatible with acute haemorrhage. Aspirin was held for four weeks, and she was discharged after completing rehabilitation. Her baseline mobility had disimproved and she required assistance and a frame on discharge. Conclusion: IPT rupture and psoas haematoma are atypical causes of atraumatic hip pain in older adults. Nevertheless, they can cause significant disability. MRI is recommended as the gold standard for diagnosis. Treatment is commonly conservative, focused on physiotherapy and pain control to maintain mobility. While aspirin is not commonly associated with tendon rupture or haemorrhage, it is widely used in primary prevention of cardiovascular disease and due consideration should be given to stopping it following the occurrence of haemorrhage.